Accountable care organizations: a strategy for future success?. Issue 2 (11th June 2018) - Harrison, Jeffrey; Spaulding, Aaron; Harrison, Debra A.
Abstract : Purpose: The purpose of this paper is to assess the community dynamics and organizational characteristics of US hospitals that participate in accountable care organizations (ACO). Design/methodology/approach: Data were obtained from the 2015 American Hospital Association annual survey and the 2015 medicare final rule standardizing file. The study evaluated 785 hospitals which operate ACO in contrast to 1, 446 hospitals without an ACO. Findings: In total, 89 percent of hospitals using ACO's are located in urban communities and 87 percent are not-for-profit. Hospitals with a higher case mix index are more likely to have an ACO. Practical implications: ACOs allow healthcare organizations to expand their geographic markets, achieve greater efficiencies, and enhance the development of new clinical services. They also shift the focus of care from acute care hospitalization to the full continuum of care. Originality/value: This research found ACOs with hospital and physician networks are an effective mechanism to control healthcare costs and reduce medical errors.